HbA1c as a predictor for response of bevacizumab in diabetic macular oedema. Issue 1 (12th May 2020) - Sharma, Sadhana; Joshi, Sagun Narayan; Karki, Pratap
Abstract : Objective: To study the influence of glycosylated haemoglobin (HbA1c) on response of bevacizumab in patients with diabetic macular oedema. Methods and Analysis: A total of 37 eyes of 37 patients with vision loss due to diabetic macular oedema treated with bevacizumab were included in this study. Participants received monthly intravitreal bevacizumab (0.05 mL/1.25 mg) for 3 months. Results: There were 17 patients with baseline HbA1c ≤7% (< 53mmol/mol) and 20 patients with baseline HbA1c >7% (>53mmol/mol) treated with bevacizumab included in the study. The mean improvement in visual acuity at 3 months was 0.50 logMAR in HbA1c ≤7%(< 53mmol/mol) group and 0.33 logMAR in HbA1c >7%(>53mmol/mol) group (95% CI, -0.05-0.38; p=0.13). The mean central macular thickness (CMT) reduction was −229.76 µm in patients with a baseline HbA1c ≤7% (< 53 mmol/mol) and −145.20 µm in patients with HbA1c of >7% (>53mmol/mol) (95% CI, 12.98-156.14; p=0.022). Conclusion: Our study suggests that baseline glycaemic control can affect the treatment outcome of intravitreal bevacizumab in the management of diabetic macular oedema and the response was found to be better in patients with good glycaemic control (low HbA1c).